THE THEORY OF CREATING ARTISTIC IMAGERY - Abdullaeva Mukhlisa (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. The theory of creating artistic images is a basic concept in the study of literature, visual arts, and other creative disciplines. In this article, I shall try to explore the various approaches and techniques used in the construction of artistic imagery which focus on its role in conveying meaning, emotions, and cultural messages. Artistic images, whether verbal or visual, are central to the creative process, serving as vehicles for both aesthetic expression and conceptual exploration. I shall also examine the historical development of artistic imagery, drawing on the works of key theorists and practitioners, and investigates how these images are shaped by cultural, social, and psychological factors. Furthermore, the interaction between the creator and the audience, highlighting how imagery can influence perception and interpretation will be considered. Finally, the study explores the role of metaphor, symbolism, and other literary devices in the creation of artistic images. By analyzing various case studies, the article provides insights into the dynamic relationship between artistic creation and the theoretical frameworks that support it, shedding light on the essential role that artistic imagery plays in both artistic practice and the broader cultural landscape.